1995
DOI: 10.1007/bf00200391
|View full text |Cite
|
Sign up to set email alerts
|

Arteriohepatic dysplasia (Alagille's syndrome): unusual hepatic architecture and function

Abstract: A diagnosis of Alagile's syndrome is suggested when a large, deformed and somewhat spherical liver is encountered, especially when hepatobiliary imaging studies demonstrate delayed excretion of radiopharmaceutical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The reported radiologic appearances of AGS are diverse and previous studies demonstrated a much higher rate of hepatic parenchymal changes when compared with our data. Halvorsen et al [ 19 ] observed spherical hepatic deformity in 63% (5/8) of AGS patients. Berrocal et al [ 20 ] reported that 68% (19/28) of AGS patients showed hepatomegaly, fibrosis, or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported radiologic appearances of AGS are diverse and previous studies demonstrated a much higher rate of hepatic parenchymal changes when compared with our data. Halvorsen et al [ 19 ] observed spherical hepatic deformity in 63% (5/8) of AGS patients. Berrocal et al [ 20 ] reported that 68% (19/28) of AGS patients showed hepatomegaly, fibrosis, or cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…AGS is progressive cholangiopathy, and the prevalence and severity of PIBD can increase with increasing age as a result of retained toxins, inflammation, or disuse atrophy. The age of patients in previous studies range from 3 months to 33 years [ 19 , 20 ], and therefore included an older age group than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in adults, where HCC is usually seen with underlying liver disease, only 20–35% children with HCC children have underlying liver disease (65). Some childhood disorders predisposing to HCC are biliary atresia (66), BSEP deficiency (32), GSD type I (67), tyrosinemia (68), α1-antitrypsin deficiency (69), and Alagille syndrome (70). Fibrolamellar HCC is a distinct pathologic variant usually affecting adolescents and young adults without an underlying liver disease; better survival in this entity is presumably due to the young age of the patients and the lack of cirrhosis making aggressive surgical resections possible (71).…”
Section: Liver Tumorsmentioning
confidence: 99%
“…Liver morphology may be abnormal, and, when associated with delayed excretion of radionuclide tracer, suggests the diagnosis of Alagille's [66]. Liver morphology may be abnormal, and, when associated with delayed excretion of radionuclide tracer, suggests the diagnosis of Alagille's [66].…”
Section: Syndromic Paucity Of Interlobular Bile Ductsmentioning
confidence: 99%